APPLICATION OF STRESS SELECTION INDICES FOR ASSESSMENT OF NITROGEN TOLERANCE IN WHEAT (Triticum aestivum L.) - F. U. Khan; F. Mohammad (Journal of Animal and Plant Sciences, 2016)
To identify desirable genotypes best suited to limited nitrogen availability based on stress selection indices, thirty wheat varieties were field tested under with (N+) and without nitrogen (N0) conditions at New Developmental Research Farm, The University of Agriculture Peshawar, Pakistan during 2013-14 crop season. Fifteen stress tolerance indices viz. tolerance index (TOL), mean productivity (MP), harmonic mean (HM), stress susceptibility index (SSI), geometric mean productivity (GMP), stress tolerance index (STI), yield index (YI), yield stability index (YSI), low nitrogen tolerance index (LNTI), nitrogen stress index (NSI), nitrogen index (NI), stress susceptibility percentage index (SSPI), modified stress tolerance index (MSTI= K1STI and K2STI), relative nitrogen index (RNI) were computed based on grain yield of each genotype under stress (N0) and non-stress (N+) conditions. Grain yield under both stress and non-stress condition had positive association with MP, GMP, HM, and STI and could be used as better indicator for screening wheat genotypes for nitrogen tolerance. In addition, TOL, SSI, LNTI, NSI, SDI, SSPI and K1STI had significant positive relationship with grain yield under non-stress, while NI had positive correlation with grain yield under stress condition. Cluster analysis showed genotypes Tatara-96, Pirsabak-05,and Shahkar-13 as tolerant, whereas, genotypes Faisalabad-08, NARC-11, Aas-11-11, Khyber-87, Pirsabak-08, Punjab-11, Atta Habib, Ghaznavi-98, Saleem-2000, Sulaiman-96, Sehar-06, ARRI, and Janbaz-09 as semi tolerant and Pirsabak-04, Dharabi-11, Bathoor-08-08, Barsat-10, Watan-93, Pirsabak-13, Nowshehra-96, Amin-10, Siran-10, Pirsabak-85 and Kohat-2000 as semi susceptible. Similarly, Inqilab-91, Hasham-08 and Pak-81 as nitrogen stress sensitive. Principal component analysis (PCA) and three dimensional bi-plot partitioned genotypes into four groups. Group A included genotypesTatara-96, Shahkar-13, Pirsabak-05, Saleem-2000, Ghaznavi-98, Sehar-06, Janbaz-09 and Suleeman-96. Group-B included Khyber-87, Aas-11-11, NARC-11, Faisalabad-08, Atta Habib, Punjab-11, ARRI, and Pirsabak-08. Group C included genotypes KT-2000, Pirsabak-85, Nowshehra-96, Amin-10, Siran-10, Pirsabak-13and Group D comprised genotypesInqilab-91, Hasham-08, Pak-81, Pirsabak-04, Dharabi-11, Barsat, Bathoor-08 and Watan-93. Based on multiple analysis, wheat genotypes viz.Tatara-96, Pirsabak-05, and Shahkar-13, were found tolerant to nitrogen stress and could be used as parents in hybridization scheme for development of nitrogen use efficient cultivars.
Keywords: Wheat; stress selection indices; nitrogen tolerance; principal component analysis